The association of postnatal urinary tract dilation risk score with clinical outcomes. Issue 4 (August 2019) - Nelson, C.P.; Lee, R.S.; Trout, A.T.; Servaes, S.; Kraft, K.H.; Barnewolt, C.E.; Logvinenko, T.; Chow, J.S.
Summary: Background: There are limited data on the predictive value of the consensus urinary tract dilation (UTD) score with respect to subsequent clinical diagnoses. We sought to define the relationship between postnatal UTD risk score and clinical outcomes during childhood. Methods: Complete ultrasound image sets from a random selection of infants aged 0–90 days undergoing initial ultrasound at a single institution for prenatal hydronephrosis between 2012 and 2014 were assigned a UTD score by 1 pediatric urologist and 1 pediatric radiologist. Urinary tract dilation risk score was analyzed for association with a composite outcome comprising urinary tract infection, vesicoureteral reflux (VUR), ureteropelvic junction obstruction, non-refluxing megaureter (NRM), ureterocele, bladder outlet obstruction (BOO), and chronic kidney disease. Surgical intervention and resolution of UTD were evaluated separately. Descriptive and survival analyses were performed. Results: Urinary tract dilation scores for 494 subjects were P0 in 23.5%, P1 in 26.5%, P2 in 23.5%, and P3 in 26.5%. Seventy-four percent were male. Median age at initial imaging was 28 days; median follow-up was 19.8 months. The composite outcome occurred in 138 of 494 patients (27.9%) and varied significantly (p < 0.001) by UTD score: 11.2% for P0, 10.7% for P1, 29.3% for P2, and 58.8% for P3. On survival analysis (Summary Figure), higher UTD grade was significantly associated with the composite outcome (hazard ratio for P3 vs. P0 was 7.4 [95% CI: 3.44–15.92, p < 0.001]). Urinary tract infection and VUR diagnosis varied by UTD score (p = 0.03 and p < 0.001, respectively). Ureteropelvic junction obstruction was diagnosed (based on MAG3 results) in 6.3% of patients, 84% of whom were P3. Non-refluxing megaureter was diagnosed in 7.7%. Ureterocele and BOO were uncommon (1.4%, and 0.6%, respectively). Surgical intervention was also associated with UTD risk, with 46% of P3 undergoing surgery vs. 1% of P0, 1% of P1, and 6% of P2 (p < 0.001). Resolution of UTD occurred in 41% (median 10.1 months) and varied significantly by UTD risk (p < 0.001). Discussion: Urinary tract dilation risk score is associated with clinical events, although ascertainment bias may influence some of the differences in outcomes, particularly for VUR, because VCUG utilization varied by the UTD group. The lack of any significant difference in outcomes between patients with UTD P0 versus P1 suggests that the P1 category could be eliminated as it does not meaningfully distinguish between outcome risk. Conclusions: Higher UTD risk scores are strongly associated with genitourinary diagnoses during the first two years of life. Summary Fig. Composite event-free survival (in months) based on Cox proportional hazards model, for UTD grades P0-P3. Composite event included any of the following: urinary tract infection, diagnosis of vesicoureteral reflux (VUR) grade > II, diagnosis of ureteropelvic junction obstruction (MAG3 halftime >20 mins or function < 40%), nonrefluxing megaureter (ureteral diameter > 7m or "moderate" dilation in absence of VUR), bladder outlet obstruction, ureterocele, or chronic kidney disease. P-value from Cox model corresponds to association of risk groups with event-free survival. Summary Figure